HUBUNGAN STATUS GIZI DAN HIPERTENSI DENGAN KEJADIAN MOLA HIDATIDOSA DI RSUD BANJARNEGARA TAHUN 2011 – 2013 - Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Hydatidiform mole is the most gestational trophoblastic disease. The data obtained in Banjarnegara General Hospital for the last three years shows that there is an increase of molahidatidosa incidence. In 2011 there were 12 occurrences of hydatidiform mole (0.27%), in 2012 there were 14 hydatidiform mole events (0.29%) and in 2013 there were 17 incidents of hydatidiform mole (0.32%). Factors that affect the hydatidiform mole include the nutritional status and hypertension. The purpose of this study is to know the relationship between nutritional status and hypertension with the occurrence of hydatidiform mole. This research type is analytic survey with case control approach. The population in this study were pregnant women who experienced hydatidiform mole in 2011-2013 in midwifery poly in Lotus room 43 people and who did not experience hydatidiform mole as many as 14,720 people. The sample of this study is pregnant women who experience hydatidiform mole of 43 people and who did not experience hydatidiform mole as much as 43 people. Data analysis using chi-square. Results: Pregnant women in the case group had more nutritional status either more ie 24 (41.4%). Pregnant women in the case group who experienced hypertension was 22 (51.2%) While in the control group, pregnant women who did not have hypertension is 36 (83.7%). There is a relationship between nutritional status and the occurrence of hydatidiform mole and there is a correlation between hypertension and the occurrence of hydatidiform mole. Conclusion: There is a relationship of parity and hypertension with the occurrence of hydatidiform mole at RSUD Banjarnegara Year 2011-2013. Keywords: Nutrition Status, Hypertension, Hydatose Mola